2019
DOI: 10.1042/bsr20182371
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and adverse reaction to different doses of atorvastatin in the treatment of type II diabetes mellitus

Abstract: Background: Type II diabetes mellitus (T2DM), a persistent metabolic disorder, is primarily characterized by insulin resistance, relative insulin deficiency and dyslipidemia. Here, we aimed to investigate whether different doses of atorvastatin (ATV) affect rats with T2DM. A total of 110 Sprague–Dawley rats were successfully established as T2DM models. Methods: First, the total cholesterol, triglyceride (TG), high-/low-/very-low-density lipoprotein cholesterol (HDL-c/LDL-c/VLDL-c), alanine transaminase (ALT), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
3
3
0
Order By: Relevance
“…While tea tree essential oil showed a good antibacterial activity in nearly all bacterial isolates and strains of E. coli and S. aureus , other essential oils used in our study showed a constrained antibacterial activity contrary to the test bacterial isolates according to the obtained MIC values. Our result was similar to other findings that have reported antibacterial activity [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Resultssupporting
confidence: 93%
“…While tea tree essential oil showed a good antibacterial activity in nearly all bacterial isolates and strains of E. coli and S. aureus , other essential oils used in our study showed a constrained antibacterial activity contrary to the test bacterial isolates according to the obtained MIC values. Our result was similar to other findings that have reported antibacterial activity [ 52 , 53 , 54 , 55 , 56 ].…”
Section: Resultssupporting
confidence: 93%
“…Indeed, a clinically significant druginduced liver injury by statins is very rare (Einar et al, 2012). Our results show that a high dose of atorvastatin caused an elevation in ALT and AST levels which agrees with Jiang & Zheng (2019) who showed that rats administered atorvastatin at a dose of 80 mg per kg daily exhibited higher levels of AST and ALT, and is consistent with the study of Abed Al-kareem et al, (2020) who observed a significant increase in ALT and AST concentration in albino rats administered atorvastatin for 60 days as many drugs overdoses cause liver injury and elevate levels of liver enzymes biomarkers. Most drug-induced liver injuries induced by statins are a consequence of the idiosyncratic effect.…”
Section: Histopathological Resultssupporting
confidence: 91%
“…Atorvastatin at dose (10) & (20) mg per kg, single dose per body weight depended on (Panonnummal et al, 2014). Atorvastatin dose (40) mg per kg, single dose per body weight depended on (Jiang & Zheng, 2019). Atorvastatin dose (150) mg per kg, single dose per body weight depended on (Reddy et al, 2010).…”
Section: Preparation Of Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atorvastatin had no effect on FPG levels but reduced cholesterol, TG, LDL-C, and HDL-C levels. This is in accordance with studies that showed reduced TG and cholesterol levels of atorvastatin in mice when administered at either low (10 mg/kg) or high doses (80 mg/kg) [47,48]. In the present study, combining GRT with atorvastatin did not enhance the efficacy of…”
Section: Plos Onesupporting
confidence: 93%